METHOD FOR ISOLATING VIRUS - Mel, Maizirwan; Ibrahim, Adelina (2012)
A METHOD FOR ISOLATING VIRUS, IN PARTICULARLY, NEWCASTLE DISEASE VIRUS FROM TISSUE CULTURE AND OTHER IMPURITIES BY EMPLOYING ULTRACENTRIFUGATION. THE ISOLATED NEWCASTLE DISEASE VIRUS IS THEN USED IN FURTHER RESEARCH FOR THE PRODUCTION OF AN EFFECTIVE VACCINE AGAINST ITSELF